PENGARUH PENGGUNAAN QRIS UNTUK MENINGKATKAN EFEKTIFITAS DAN EFISIENSI PEMBAYARAN UMKM DI MEDAN - Fatma Hairani; Rapita Damanik; Adhe F Budhi; Dery Pristiwanda; Anggi P Rizki L; Diwayana Putri Nasution (Jurnal Ekonomi Manajemen Dan Bisnis (JEMB), 2024)
Bank Indonesia launched a payment system called QRIS (Quick Response Code Indonesian Standard) which is a simplification of various QR Codes to make the payment system easier and more efficient. Many people do not know this payment system and still choose to use cash. So the aim of this research is to find out what influences individuals to use the QRIS payment system. This study is a qualitative descriptive study using a literature method through literature study sourced from journals resulting from previous research. By showing the research results, namely that the existence of QRIS has a good influence on MSME players in the form of effectiveness and efficiency in digital transactions. By saving time from having to look for change, this can further increase productivity for MSMEs, especially when carrying out large digital transactions so that unwanted technical errors do not occur.